Identification of a Neuropeptide S Responsive Circuitry Shaping Amygdala Activity via the Endopiriform Nucleus - Meis, Susanne (Public Library of Science, 2008)
Neuropeptide S (NPS) and its receptor are thought to define a set of specific brain circuits involved in fear and anxiety. Here we provide evidence for a novel, NPS-responsive circuit that shapes neural activity in the mouse basolateral amygdala (BLA) via the endopiriform nucleus (EPN). Using slice preparations, we demonstrate that NPS directly activates an inward current in 20% of EPN neurons and evokes an increase of glutamatergic excitation in this nucleus. Excitation of the EPN is responsible for a modulation of BLA activity through NPS, characterized by a general increase of GABAergic inhibition and enhancement of spike activity in a subset of BLA projection neurons. Finally, local injection of NPS to the EPN interferes with the expression of contextual, but not auditory cued fear memory. Together, these data suggest the existence of a specific NPS-responsive circuitry between EPN and BLA, likely involved in contextual aspects of fear memory.